Optimalisasi Peran Library dalam Mendukung Program Musik TV pada MNC Channel - Fadhila Faella Sufa; Astuti, Vivien Febri (Universitas Islam Balitar, 2025)
This study investigates the Library Division's role in supporting MNC Channels' TV Music programs and the challenges encountered. Employing a descriptive qualitative method, with data from interviews, observation, and literature review, the research reveals the Library's crucial function in providing content for smooth production. Its responsibilities include managing, classifying, and updating digital catalog data, alongside supplying relevant, quality material. However, the division faces significant hurdles: limited human resources, technical issues with digitalization and storage, suboptimal communication with production teams, and cataloging/legality challenges. Production deadlines, insufficient staff training, and budget constraints also impede effectiveness. The study concludes that optimizing the Library's role is vital for production efficiency and broadcast quality, necessitating improvements in internal competence, technology infrastructure, metadata systems, and coordination with production teams.